Cytotoxic properties of rhenium(i) tricarbonyl complexes of N-heterocyclic carbene ligands. Issue 19 (5th May 2022) - Wiratpruk, Nuchareenat; Bindra, Guneet K.; Hamilton, Alex; Hulett, Mark D.; Barnard, Peter J.
Abstract : Eight rhenium(i ) N-heterocyclic carbene complexes in combination with N -acetyl amino acids ligands have been synthesised. The aquation rate constants for the complexes were evaluated and these compounds were cytotoxic in three cancer cell lines. Abstract : A family of eight rhenium(i ) tricarbonyl complexes bearing pyridyl-imidazolylidene or bis-imidazolylidene ligands in combination with a series of N -acetyl amino acids ligands (glycine, isoleucine, and proline) and an acetate have been synthesised and characterised. These complexes are of interest as potential anticancer agents, where the oxygen bound carboxylate ligand can exchange with water giving rise to cytotoxic cationic complexes. The pseudo-first-order aquation rate constants for the complexes were evaluated using 1 H NMR time-course experiments and for the complexes of the bis-imidazolylidene ligand the average k 1 value was 6.22 × 10 −5 s −1 while for the pyridyl-imidazolylidene ligand the aquation rate was slower with the average k 1 value being 3.00 × 10 −5 s −1 . Cytotoxicity studies in three cancer cell lines (MDA-MB-231, PC3 and HEPG2) showed that the Re(i ) complexes of the bis-imidazolylidene ligand were significantly more toxic than those of the pyridyl-imidazolylidene ligand.